Building Knowledge Management-based Systems: Initiatives at Research Centre Imarat - N., Venkatesh; S., Kalpavalli (DESIDOC Journal of Library & Information Technology, 2014)
Information technology (IT) and knowledge society are two important driving forces of 21st century. Internet and web-based technologies have led to a new era of knowledge creation, storage, retrieval and dissemination of information. During the last decade, knowledge management (KM) has been identified as the major management initiative that will help organisations, institutions, libraries and information centres to utilise fruits of IT in fulfilling the objectives of the organisation. Knowledge creation and sharing are widely recognised as important assets of any organisation. In today’s context, IT-based services have changed the entire process of information cycle. All library professionals must redesign and reshape the traditional library management tools and apply KM concepts and practices for providing better library services. Since knowledge is a critical asset of any organisation, KM practices will lead to provide right information to right person at right time into a reality. This paper covers KM concepts, changing role of library professionals and current trends in KM practices and information services in DRDO and in Research Centre Imarat (RCI) in particular. http://dx.doi.org/10.14429/djlit.34.5841